Acceptance of the Public Interest in the Judiciary of the Federal Supreme Court in Iraq - Talib, Musadaq (Journal of Legal Sciences, 2025)
This research addresses the public interest within the framework of constitutional law, as some constitutional courts, including the Federal Supreme Court in Iraq, have tended to accept the public interest and replace it with personal interest in appeals filed regarding the unconstitutionality of laws or regulations or the invalidity of federal decisions or procedures.This research tries to show the standards followed by the court regarding the acceptance of public interest in Iraq, which were represented by election laws, legislative omissions, and public prosecution appeals, in addition to analyzing the judicial trends of the Federal Supreme Court in the decisions issued by it regarding appeals submitted by members of the House of Representatives, as they are representatives of the people. Reviewing the constitutional and legal arguments and grounds on which the court relied in accepting the public interest as a condition for appeal and abandoning it in modern trends.